Recrafting the Model of the Portuguese Nun in England: Aphra Behn and Delarivier Manley´s Letter Fictions - Villegas-López, Sonia (International Journal of English Studies, 2024)
The first English translation of Lettres portugaises was published in 1678 as Five Love-Letters from a Nun to a Cavalier. Capitalising on its literary success, the nun’s letters were extended and revised in two sequels. Their influence on women’s autochthonous fiction was strong in the years that followed. I will first focus on the history of the English reception of these French works to concentrate afterwards on two texts: Aphra Behn’s Love-Letters between a Nobleman and His Sister (1684-85) and Delarivier Manley’s Letters (1696). Whereas the former questions the veracity of the love letter by exploring the artificiality of love discourses and their dangerous effects on women’s lives, the latter recrafts the tradition of the female complaint by choosing a protagonist who voices her lament on the run. The reproducibility of the nun’s model makes us read Portuguese Letters not merely as the expression of unbidden emotion, but as a letter manual that could be revised and adapted.